2021
DOI: 10.3389/fonc.2021.707705
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of the Prognostic Value of Serum Albumin to Globulin Ratio in Patients With Cancer Cachexia: Results From a Large Multicenter Collaboration

Abstract: BackgroundRecently, albumin–globulin ratio (AGR), a serological indicator that reflects nutritional status and systemic inflammatory, has been reported to be associated with the prognosis of various cancers. However, there is currently no research report on its relationship with cancer cachexia.ObjectivesThis study aimed to explore the prognostic value of AGR in patients with cancer cachexia through a multicenter retrospective analysis.MethodsWe recruited 2,364 patients with cancer cachexia and randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The AGR, which takes both albumin and globulin into account, is a convenient serological indicator to identify serum protein abnormalities [ 27 ]. Several studies indicated that it could reflect not only a change in nutritional condition, but also a medium to long-term inflammatory status [ 27 , 28 ]. Literatures reported AGR could serve as a diagnostic biomarker for infection diseases, or a prognostic marker for various types of cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AGR, which takes both albumin and globulin into account, is a convenient serological indicator to identify serum protein abnormalities [ 27 ]. Several studies indicated that it could reflect not only a change in nutritional condition, but also a medium to long-term inflammatory status [ 27 , 28 ]. Literatures reported AGR could serve as a diagnostic biomarker for infection diseases, or a prognostic marker for various types of cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin and globulin reflect the nutritional and inflammatory status of individuals and have shown potential prognostic value in a variety of tumors ( 39 41 ). On the one hand, albumin reflects the nutritional status of individuals, and in general, patients with poor nutritional status have a higher risk of postoperative complications, which may greatly shorten the survival time of cancer patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected to measure serum markers, namely, CRP, neutrophils (N), lymphocytes (L), platelets (P), glucose (Glu), albumin (ALB), and globulin (GLB). These baseline inflammatory markers constituted the following ratios and indices: NLR (N/L ratio) ( 13 ), PLR (P/L ratio) ( 13 ), prognostic nutrition index (PNI), 10 × ALB + 0.005 × L) ( 13 ), systemic immune-inflammation index (SII), P × NLR) ( 13 ), ALI (BMI × ALB/NLR) ( 13 ), CAR (CRP/ALB ratio) ( 17 ), AGR (ALB/GLB ratio) ( 18 ), LCR (L/CRP ratio) ( 14 ), GNRI (1.489 × ALB + [Present body weight (PBW)/Ideal body weight (IBW)]) ( 12 ), mGNRI (modified GNRI, 1.489 × CRP + 41.7 × PBW/IBW) ( 12 ), and nutritional risk index (NRI), 1.519 × ALB + 41.7 × PBW/IBW) ( 19 ). IBW was evaluated using the Lorentz equation: men = height (cm) − 100 − [(height − 150)/4]; women = height (cm) − 100 − [(height − 150)/2.5] ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected to measure serum markers, namely, CRP, neutrophils (N), lymphocytes (L), platelets (P), glucose (Glu), albumin (ALB), and globulin (GLB). These baseline inflammatory markers constituted the following ratios and indices: NLR (N/L ratio) (13), PLR (P/L ratio) (13), prognostic nutrition index (PNI), 10 × ALB + 0.005 × L) (13), systemic immune-inflammation index (SII), P × NLR) (13), ALI (BMI × ALB/NLR) (13), CAR (CRP/ALB ratio) (17), AGR (ALB/GLB ratio) (18), LCR (L/CRP ratio) (…”
Section: Assessment Of Inflammatory Markersmentioning
confidence: 99%